Design and synthesis method of supercritical carbon dioxide fracturing fluid sand-carrying reinforcing agent
Through molecular simulation design and photoinduced polymerization reaction, the problem of poor sand carrying performance of supercritical carbon dioxide fracturing liquid is solved, and its sand carrying capacity and penetration are improved. It is suitable for the development of shale gas reservoirs. , meets environmental protection and economic requirements.
Patent Information
- Application Number
- CN202411260501.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-17
AI Technical Summary
The poor sand carrying performance of supercritical carbon dioxide fracturing fluid in shale gas reservoirs, large friction gradients, and difficult phase control, resulting in the inability to effectively carry proppant to reach the predetermined position, which may cause sand blockage and affect the construction effect.
The supercritical carbon dioxide fracturing liquid sand carrying enhancer is designed by molecular simulation, and binary copolymers are synthesized through photoinduced solution polymerization reaction, and the viscoelasticity and CO2 functional groups are used to improve viscoelasticity, reduce friction resistance, and enhance sand carrying performance.
It improves the sand carrying performance of supercritical carbon dioxide fracturing fluid, reduces friction resistance, ensures the penetration and seam capacity of fracturing fluid, avoids sand blockage, and meets environmental protection and economic requirements.
Smart Images

Figure CN119152978A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas field production enhancement and transformation, in particular to a design and synthesis method of a supercritical carbon dioxide fracturing fluid sand-carrying enhancer. Background Art
[0002] In order to obtain abundant shale gas resources, hydraulic fracturing is currently the main technology for developing shale reservoirs. However, as the focus of domestic exploration and development research shifts to unconventional reservoirs, the water-based fracturing fluid commonly used in hydraulic fracturing technology can no longer meet the fracturing needs in various complex formations. It is urgent to promote the growth of unconventional oil and gas production through the application of new materials and new technologies. Taking shale reservoirs as an example, shale gas reservoirs are usually developed by "horizontal wells + large-scale volume fracturing", which not only consumes a large amount of water, but also may cause damage to shale reservoirs with high clay content. This has resulted in the further promotion of the slick water fracturing fluid system in the fracturing of shale gas reservoirs being restricted. Therefore, waterless fracturing technology has become a hot spot and difficulty in the field of shale gas development research.
[0003] In the mechanism research, it was found that supercritical carbon dioxide fracturing fluid (SC-CO2) can reduce the fracture pressure, connect the natural fractures of the reservoir, and promote methane desorption through complex physical and chemical effects. It has significant advantages such as enhancing the production increase and transformation effect and realizing CO2 utilization. However, at present, supercritical carbon dioxide fracturing fluid still has problems such as poor sand carrying performance, large friction gradient, and difficult phase control that need to be solved urgently. Poor sand carrying performance may cause the fracturing fluid to be unable to smoothly carry the proppant to the predetermined location, so it cannot achieve the expected construction effect. In severe cases, it may cause sand blockage, resulting in the inability to carry out the construction smoothly. Summary of the invention
[0004] In view of the problems of poor sand carrying performance and large friction gradient of current supercritical carbon dioxide fracturing fluid, the present invention provides a design and synthesis method of a supercritical carbon dioxide fracturing fluid sand carrying enhancer. The method first designs a supercritical carbon dioxide fracturing fluid sand carrying enhancer by a molecular simulation method, and then synthesizes the sand carrying enhancer by a photo-initiated solution polymerization reaction.
[0005] The design and synthesis method of the supercritical carbon dioxide fracturing fluid sand-carrying enhancer provided by the present invention comprises the following steps:
[0006] S1. Investigate commonly used additives for CO2 fracturing fluid, extract functional group structures in the molecular structures of additives, and form a functional group library of commonly used CO2 additives. The functional group library of commonly used CO2 additives includes fluorinated acrylate groups, ether bonds, amide groups, hydroxyl groups, phenyl groups, ester groups, and urea groups.
[0007] Then, the functional group molecular model and CO2 molecular model are constructed, and the molecular distance between CO2 and each functional group and the electrostatic potential distribution are calculated. According to the calculated values of molecular distance and electrostatic potential distribution, the functional group with the strongest interaction with CO2 is selected as the CO2-philic functional group, and the functional group with the weakest interaction with CO2 is selected as the CO2-phobic functional group. Specifically, the calculated molecular distance values between CO2 and each functional group are sorted in order from small to large, and the functional group corresponding to the minimum molecular distance is selected as the CO2-philic functional group; then the two functional groups corresponding to the molecular distance values ranked last are selected, and the electrostatic potential distribution of these two functional groups is further compared, and the functional group with the largest difference between the highest electrostatic potential and the lowest electrostatic potential is selected as the CO2-phobic functional group, which is conducive to the interaction between the CO2-phobic functional groups between different polymers, entanglement and formation, and improving the viscoelasticity of the system.
[0008] S2. According to the CO2-philic functional groups and the CO2-phobic functional groups, the optimal CO2-philic functional groups and the optimal CO2-phobic functional groups, as well as the molar ratio of the two functional groups, are further screened out through molecular simulation; specifically, the following two steps are included:
[0009] S21, select a plurality of functional groups with similar molecular structures to the CO2-philic functional group to form a CO2-philic functional group group. Select a plurality of functional groups with similar molecular structures to the CO2-phobic functional group to form a CO2-phobic functional group group. Combine various functional groups in the CO2-philic functional group group with various functional groups in the CO2-phobic functional group group in pairs to construct a series of binary copolymer molecular models.
[0010] S22. Construct respectively a mixed molecular model and a shear motion model of the binary copolymer obtained in step S21 and supercritical carbon dioxide; based on the calculation results of the two models, evaluate the comprehensive performance of all binary copolymers, screen out the binary copolymer with the best performance, and then obtain the CO2-philic functional groups and CO2-phobic functional groups corresponding to the binary copolymer, that is, the optimal CO2-philic functional groups and the optimal CO2-phobic functional groups; then further study the comprehensive performance of the binary copolymers obtained with different molar ratios of the optimal CO2-philic functional groups and the optimal CO2-phobic functional groups, and select the optimal molar ratio.
[0011] The ratio of the binary copolymer to the CO2 molecule in the mixed molecular model is 1-10:500-1000; the shear motion model consists of upper and lower walls and an intermediate fluid layer, the intermediate fluid layer is a mixed molecular model, the upper and lower walls are 316L stainless steel, and the length, width and height are respectively
[0012] In the mixed molecular model, the polymer solubility is judged by the simulation results of radial distribution function, interaction energy and cohesive energy density parameters; the viscoelasticity of the system is characterized by viscosity increase multiple, elastic modulus and yield stress parameters to judge the sand carrying capacity of the polymer; the ability of the copolymer to reduce friction is judged by friction shear stress; the safety, environmental protection and economy of the copolymer are judged according to the safety and environmental rating parameters and the monomer price; and the best binary copolymer is selected by comprehensive weighting.
[0013] Steps S1 and S2 are both completed using Materials Studio software.
[0014] S3. According to the optimal CO2-philic functional group screened out in step S22, a monomer containing the functional group is selected as a CO2-philic monomer; according to the optimal CO2-phobic functional group screened out in step S22, a monomer containing the functional group is selected as a CO2-phobic monomer; using the CO2-philic monomer and the CO2-phobic monomer as raw materials, determining the amount of the two raw monomers according to the optimal molar ratio of the optimal CO2-philic functional group and the optimal CO2-phobic functional group, and then conducting a polymerization reaction. The prepared copolymer is a sand-carrying enhancer.
[0015] The polymerization method is as follows:
[0016] The CO2-philic monomer and the CO2-phobic monomer are dissolved in different solvents respectively, and then the two solutions are mixed and stirred, and an initiator is added to obtain a reaction solution; the reaction solution is placed under an ultraviolet lamp to initiate a polymerization reaction, and the prepared copolymer is a sand-carrying enhancer.
[0017] Compared with the prior art, the present invention is beneficial in that:
[0018] (1) The present invention innovatively provides a method for designing a binary copolymer with the best comprehensive performance as a supercritical carbon dioxide fracturing fluid sand-carrying enhancer using molecular simulation as an auxiliary means, and then synthesizing the binary copolymer through a photoinitiated solution polymerization reaction to obtain a supercritical carbon dioxide fracturing fluid sand-carrying enhancer.
[0019] (2) The sand-carrying enhancer of the present invention is designed for supercritical carbon dioxide fracturing fluid, which overcomes the problems of poor sand-carrying performance and large friction gradient of current supercritical carbon dioxide fracturing fluid to a certain extent, and has the effect of one dose for multiple purposes. In addition, the copolymer innovatively adopts the concept of viscoelastic sand-carrying, which is different from previous studies that simply rely on viscosity to carry sand. On the one hand, it can ensure the characteristics of strong penetration and excellent fracture-forming ability of SC-CO2 fracturing fluid itself; on the other hand, it can rely on viscoelasticity to effectively carry sand.
[0020] (3) Although the binary copolymer of the present invention is a fluorine-containing polymer, the length of the fluorocarbon side chain is less than or equal to 6, and it will not be difficult to degrade in the environment, does not have biological accumulation, and will not cause damage to the core, which is in line with the concept of reservoir protection; and economic considerations have been taken into account, meeting the requirements of green economy and environmental protection in oil field applications.
[0021] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The present invention provides a design and synthesis flow chart of the supercritical carbon dioxide fracturing fluid sand-carrying enhancer.
[0023] Figure 2 This is the radial distribution function (RDF) simulation result diagram.
[0024] Figure 3 This is the result diagram of interaction energy simulation.
[0025] Figure 4 This is the simulation result diagram of cohesive energy density and solubility parameter.
[0026] Figure 5 This is the simulation result of the viscosity increase multiples of different polymers.
[0027] Figure 6 This is the simulation result of stress-strain curve of polymer-CO2 mixed system.
[0028] Figure 7 The results of solubility evaluation of polymers synthesized by polymerization reaction in SC-CO2; a) represents pure SC-CO2; b) represents when polymer is added; c) represents the process of liquid CO2 introduction; d) represents after 2 hours of heat and pressure maintenance cycle; e) represents 10MPa; f) represents 15MPa.
[0029] Figure 8 This is a graph showing the sand-carrying performance test results of the polymer synthesized by polymerization reaction. DETAILED DESCRIPTION
[0030] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0031] like Figure 1 As shown, the design and synthesis method of the supercritical carbon dioxide fracturing fluid sand-carrying enhancer provided by the present invention comprises the following specific steps:
[0032] S1. Through the investigation of commonly used additives in CO2 fracturing fluid, the corresponding functional groups of the additives were extracted, and the functional group library of commonly used CO2 additives was constructed, including fluorinated acrylate groups, ether bonds, amide groups, hydroxyl groups, phenyl groups, ester groups, urea groups and other functional groups. The materials studio software was used to construct simplified molecular models of each functional group and CO2 molecular models, and the distance between CO2 molecules and each functional group molecule was calculated. In actual calculations, the distance between the lowest-charged atom in each functional group and the carbon atom in the CO2 molecule is calculated as The calculated molecular distances between CO2 molecules and each functional group and the distribution of electrostatic potential are shown in Table 1. It can be concluded from Table 1 that the molecular distance between the fluorinated acrylate group and CO2 is the smallest, and the fluorinated acrylate group is selected as the CO2-philic group of the copolymer. The molecular distance between the urea group and CO2 is the largest, followed by the ester group. In the dynamic simulation, the urea group tends to gradually move away from CO2 as the simulation proceeds, and finally the molecular distance between the urea group and CO2 is the largest, showing obvious CO2-phobic characteristics. However, from the perspective of electrostatic potential distribution, the electrostatic potential on the oxygen atom in the urea group is the lowest (-0.082Ha·e -1 ), and the H atom connected to the N atom on the urea group has the highest positive potential (0.088 Ha·e -1 ), so the molecules are more likely to combine with each other, which is conducive to the construction of a spatial network structure, so urea groups are selected as CO2-phobic groups to be introduced into the copolymer structure. Therefore, fluorinated acrylate groups are used as the CO2-philic groups of the copolymer, and urea groups are used as the CO2-phobic groups of the copolymer.
[0033] Table 1. Quantum chemical simulation results
[0034]
[0035] S2. Based on the fluorinated acrylate groups, four different fluorinated acrylate groups, mFA4, mFA6, mFA8, and mFA10, were selected as alternative CO2-philic functional groups. mFA4 represents a fluorinated acrylate group with a 4-FC chain length; mFA6 represents a fluorinated acrylate group with a 6-FC chain length, and the molecular structure is as follows:
[0036]
[0037] Similarly, mFA8 and mFA10 represent fluorinated acrylate groups with 8 and 10 FC chain lengths, respectively. The molecular structures of the four functional groups mFA4, mFA6, mFA8, and mFA10 are similar, except for the different CF chain lengths.
[0038] Since the urea-containing polymer monomer is mainly allyl urea, it is often used as a synthetic raw material and preservative for allyl thiourea in the chemical industry and has acute toxicity, while allyl thiourea, which has similar properties, is more widely used and relatively inexpensive. Therefore, in this embodiment, mN and mNS are selected as alternative CO2-dispersing functional groups. The molecular structures of mNO and mNS are as follows:
[0039]
[0040] According to previous studies, the longer the FC chain length, the stronger the interaction between the substance and CO2. However, the longer the FC chain length, the greater the toxicity. According to the environmental protection requirements of this industry, fluorinated substances with more than 6 FC chains do not meet the environmental protection requirements and are not recommended for use. Based on these two reasons, mFA6 is preliminarily determined as the optimal CO2-philic functional group in the present invention.
[0041] The binary copolymer models of pFA6NS and pFA6NO were constructed by using mFA6 with mNO and mNS respectively. At the same time, a homopolymer model without CO2-repelling functional groups and formed only by the polymerization of mFA6 was constructed, namely the pFA6 model.
[0042] The mixed molecular models and shear motion models of the three copolymers pFA6NS, pFA6NO, and pFA6 with supercritical carbon dioxide (SC-CO2) were constructed respectively. Based on the calculation results of these two models, the comprehensive performance of the copolymers was evaluated and the copolymer with the best performance was screened out.
[0043] The mixed molecular model of polymer and SC-CO2 and the shear motion model constructed in this embodiment are as follows:
[0044] The molecular ratio of supercritical carbon dioxide (SC-CO2) to polymer is 750:3.
[0045] The shear motion model of the polymer and SC-CO2 was constructed, and the length, width, and height of the upper and lower walls were For single-phase austenitic stainless steel 1Cr18Ni9Ti, use Build Layer to establish the shear motion configuration, select 316L as the BOTTOMWALL layer and TOPWALL layer, and the mixed model of SC-CO2 and polymer as the intermediate FLUID layer. In the Options tab, check the "Configure for restrictive shear use" option, and a 20nm vacuum layer is automatically added above the upper wall layer.
[0046] The maximum number of steps for structure optimization of the hybrid molecular model and the shear motion model was set to 15,000.
[0047] The annealing process of the mixed molecular model and the shear motion model was carried out under the NVT ensemble, with the temperature range set to 300–500 K, 5 cycles, and the total simulation step size set to 50,000 steps.
[0048] The NPT ensemble was selected for the kinetic equilibrium process of the mixed molecular model. The temperature was set to 308 K, the pressure was set to 25 MPa, the simulation time was at least 2000 ps, the Velocity-Scale heat bath was used to control the system temperature, and the Parrinello-Rahman pressure bath was used to control the system pressure.
[0049] The dynamic equilibrium of the shear motion model was simulated by NPT equilibrium phase simulation for 500 ps at a temperature of 308 K. The movement of the upper and lower metal layers in the X and Y directions was restricted. The temperature was set to 308 K and the pressure was set to 25 MPa.
[0050] Shear motion model The restricted shear motion sets the relative movement speed of the metal layer in the NPT ensemble as The temperature was set to 308K, the pressure was set to 25MPa, and the simulation time was 500ps.
[0051] The temperature and pressure of the equilibrium process were controlled by Velocity-Scale heat bath and Berendsen pressure bath respectively, and the initial velocity was randomly generated by software.
[0052] The solubility of copolymers in SC-CO2 was evaluated by radial distribution function, interaction energy, and cohesive energy density, such as Figure 2-4 ; The sand-carrying capacity of the copolymer was evaluated by the viscosity increase ratio and stress-strain curve (elastic modulus, yield stress), such as Figure 5-6 ; Evaluate the economic efficiency of the monomer through the unit price of the monomer; Evaluate the environmental performance of the monomer through the safety and environmental rating parameters.
[0053] The calculation results of the optimal evaluation parameters of the three copolymers pFA6NS, pFA6NO and pFA6 are shown in Table 2. It can be concluded that the pFA6NS polymer has the best comprehensive performance. Therefore, it is preliminarily determined that mFA6 and mNS are the optimal CO2-philic and CO2-phobic functional groups, respectively.
[0054] In order to verify whether mFA6 is the optimal CO2-philic functional group, four copolymer models of pFA4NS, pFA6NS, pFA8NS and pFA10NS were constructed by using mNS and mFA4, mFA6, mFA8 and mFA10. Then, the mixed molecular model and shear motion model of the three copolymers pFA4NS, pFA6NS, pFA8NS and pFA10NS with supercritical carbon dioxide (SC-CO2) were constructed respectively. According to the calculation results of these two models, the comprehensive performance of various copolymers was evaluated. The specific method of constructing the mixed molecular model and shear motion model of polymer and SC-CO2 is the same as above. The simulation calculation results are shown in Table 3. It can be seen from Table 3 that the comprehensive performance of pFA6NS copolymer is the best. This further proves that mFA6 is indeed the optimal CO2-philic functional group.
[0055] In order to determine the effect of the molar ratio of the two functional groups of mFA6 and mNS on the performance of the polymer, the molar ratio of mFA6 and mNS was set to 4:1, 3:2, 2:3, and 1:4, respectively, and four copolymer models of pFA6NS-1, pFA6NS-2, pFA6NS-3, and pFA6NS-4 were obtained. Then, the mixed molecular model and shear motion model of these four copolymers with supercritical carbon dioxide (SC-CO2) were constructed respectively, and the comprehensive performance of various copolymers was evaluated according to the calculation results of these two models. The specific method of constructing the mixed molecular model and shear motion model of the polymer and SC-CO2 here is the same as above. The simulation calculation results are shown in Table 4. It can be seen from Table 4 that when the molar ratio of mFA6 and mNS is 3:2, the comprehensive performance of the pFA6NS-2 copolymer is the best, so the optimal molar ratio of mFA6 and mNS is determined to be 3:2.
[0056] Table 2. Calculation results of the optimal evaluation parameters for CO2-repelling functional groups
[0057]
[0058] Table 3. Calculation results of the optimal evaluation parameters for CO2-philic functional groups
[0059]
[0060] Table 4. Calculation results of comprehensive evaluation parameters for optimal molar ratio of mFA6 and mNS
[0061]
[0062] S3. According to the preferred mFA6 functional group, a monomer containing the functional group is selected as a CO2-philic monomer, and a monomer containing the mNS functional group is selected as a CO2-phobic monomer. The dosage ratio of the two monomers is determined according to the optimal molar ratio of mFA6 and mNS of 3:2, and then a polymerization reaction is carried out. The prepared copolymer is a sand-carrying enhancer.
[0063] In this embodiment, the CO2-philic monomer is perfluorohexyl ethyl acrylate, and the CO2-phobic monomer is allyl thiourea.
[0064] The polymerization method is as follows:
[0065] (1) Perfluorohexylethyl acrylate is dissolved in ethyl acetate to a solution concentration of 200 g / L; allylthiourea is dissolved in anhydrous ethanol to a solution concentration of 300 g / L, and then the two solutions are mixed and stirred, and an initiator is added to obtain a reaction liquid system; the initiator is 2-hydroxy-2-methyl-1-phenylacetone, and the amount added is 1wt% of the total mass of the two monomers.
[0066] (2) placing the reaction liquid system under ultraviolet light to initiate the reaction; the ultraviolet light irradiation time is 80 minutes;
[0067] (3) After the reaction is completed, acetone is added to precipitate, and the solvent is filtered to remove to obtain a precipitate; the precipitate is dissolved with a solvent 1,1,1-trichlorotrifluoroethane, and then acetone is added again to precipitate, and the dissolution and precipitation operations are repeated 2-3 times, and then the precipitate is dried to obtain a binary copolymer, which is a supercritical carbon dioxide fracturing fluid sand-carrying enhancer.
[0068] The solubility of the copolymers prepared by the polymerization reaction was evaluated in SC-CO2. The experimental results are shown in Figure 7 .Depend on Figure 7 It can be seen that: under the condition of circulating flow, the copolymer can be basically dissolved in SC-CO2 to form a uniform transparent solution. And in the process of increasing pressure, the solubility of the copolymer is gradually enhanced, the solubility is poor under low pressure, and the solubility is more thorough under high pressure. Under the low pressure condition of 10MPa, the copolymer is only dispersed in SC-CO2, and cannot be completely dissolved in SC-CO2, and the system is turbid; when the pressure rises to 15MPa, the system gradually becomes clear, and the copolymer is completely dissolved in SC-CO2.
[0069] The copolymer prepared by the polymerization reaction was added to SC-CO2 to carry out sand carrying performance test. The test results are shown in Figure 8 ,Depend on Figure 8 It can be seen that when there is no copolymer, the proppant particles tend to fall vertically, and the particle falling speed in the vertical direction is 9.15 cm·s -1In the copolymer-CO2 solution, due to the change in fluid properties, the magnitude of various forces acting on the proppant in the SC-CO2 solution changes, causing the proppant's falling trajectory to become disordered. During the falling process, the proppant will roll with the movement of SC-CO2, and can even move in the opposite direction under the carrying of the CO2 solution, making the vertical distance of the proppant falling in the same length of time shorter, and the average falling speed is reduced to 4.01cm·s -1 By comparison, it was found that when the addition amount of the copolymer was 3wt%, the copolymer reduced the falling speed of the proppant in SC-CO2 by more than 50%.
[0070] The prepared binary copolymer was compared with the existing viscous sand-carrying polymer for performance, and the results are shown in Table 5. As can be seen from Table 5, although the copolymer of the present invention emphasizes the concept of viscoelastic sand-carrying, it still has excellent viscosity-increasing performance compared with the existing viscous sand-carrying polymer.
[0071] Table 5 Comparison of viscosity increasing ability of different additives
[0072] Sample name Concentration (wt%) Viscosity increase ratio pFA6NS 3 10.83 pFA6NS 5 14.45 Existing viscous sand-carrying polymer 1 (Reference 1) 3.4 2.5 Existing viscous sand-carrying polymer 2 (Reference 2) 1.19-2.35 2-4 Existing viscous sand-carrying polymer 3 (Reference 3) 1.5 1.23 Existing viscous sand-carrying polymer 4 (Reference 4) 4 4.2
[0073] In Table 5, the existing viscous sand-carrying polymers 1, 2, 3, and 4 are from the following four documents:
[0074] Document 1: N. Mohammed, A. Hinai, M. Myers, CD Wood, A. Saeedi, Enhanced Oil Recovery Processes-New Technologies, IntechOpen (2019) 160.
[0075] Literature 2: P.Xue, J.Shi,
[0076] Reference 3: NMAli Hinai, A.Saeedi, C.D.Wood, M.Myers, R.Valdez, A.K.Sooud, A.
[0077] Sari, Energy & Fuels 32(2018)1600–1611, https: / / doi.org / 10.1021 / acs.energyfuels.7b03733.
[0078] Literature 4: Lemaire, PC, Alenzi, A., Lee, JJ, Beckman, EJ, Enick, RM, 2021. Thickening CO2 with direct thickeners, CO2-in-Oil emulsions, ornanoparticle dispersions: literature review and experimental validation. Energy Fuels 35, 8510–8540.
[0079] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A design and synthesis method for a supercritical carbon dioxide fracturing fluid sand-carrying enhancer, It is characterized in that Here are the steps: S1. Research CO 2 Common additives for fracturing fluids, extract the functional group structure in the molecular structure of the additives to form CO 2 Commonly used additive functional group library; Construction of functional group molecular model and CO 2 Molecular model, using quantum chemical simulation to calculate CO 2 The molecular distance and electrostatic potential distribution of each functional group are selected according to the calculated values of molecular distance and electrostatic potential distribution. 2 The most interactive functional group is the CO-philic 2 Functional group, selected from CO 2 The weakest interacting functional group acts as a CO-repellent 2 Functional groups; S2, according to step S1 selected pro-CO 2 Functional groups and CO 2 Functional groups, and the optimal CO affinity was further screened by molecular dynamics simulation. 2 Functional groups and optimal CO 2 Functional groups, and the molar ratio of the two functional groups; specifically including the following two steps: S21, select multiple 2 Functional groups with similar molecular structures have CO affinity 2 Functional group; select a variety of CO 2 Functional groups with similar structures have CO 2 Functional group; CO 2 The various functional groups in the functional group group and the CO 2 Various functional groups in the functional group group are combined in pairs to construct a binary copolymer molecular model; S22, respectively constructing a mixed molecular model and a shear motion model of the binary copolymer obtained in step S21 and supercritical carbon dioxide, and evaluating the comprehensive performance of all binary copolymers based on the kinetic calculation results of the two models, screening out the binary copolymer with the best performance, and then obtaining the CO affinity corresponding to the binary copolymer. 2 Functional groups and CO 2 Functional group, i.e., the most CO-philic 2 Functional groups and optimal CO 2 functional groups; then further study the optimal CO affinity 2 Functional groups and optimal CO 2 The comprehensive properties of binary copolymers obtained by different molar ratios of functional groups are optimized to find the best molar ratio; S3, the best affinity CO selected according to step S22 2 Functional group selection monomer containing this functional group as a CO 2 Monomer, according to the optimal CO 2-dispersible monomer selected in step S22 2 Functional group selects monomers containing this functional group as CO 2 Monomer; CO-philic 2 Monomer and CO 2 Monomers are used as raw materials, according to the best affinity for CO 2 Functional groups and optimal CO 2 The optimal molar ratio of the functional groups is used to determine the dosage of the two raw monomers, and then a polymerization reaction is carried out to prepare a copolymer, which is a sand-carrying enhancer.
2. The design and synthesis method of the supercritical carbon dioxide fracturing fluid sand-carrying enhancer according to claim 1, It is characterized in that In step S1, the CO 2 Commonly used additive functional group libraries include fluorinated acrylate groups, ether bonds, amide groups, hydroxyl groups, phenyl groups, ester groups, and urea groups.
3. The design and synthesis method of the supercritical carbon dioxide fracturing fluid sand-carrying enhancer according to claim 1, It is characterized in that In step S1, the calculated CO 2 The molecular distance values of each functional group are sorted in order from small to large, and the functional group corresponding to the smallest molecular distance is selected as the CO-philic 2 Then select the two functional groups corresponding to the last two molecular distance values, further compare the electrostatic potential distribution of these two functional groups, and select the functional group with the largest difference between the highest and lowest electrostatic potentials as the CO2-repellent. 2 Functional groups.
4. The design and synthesis method of the supercritical carbon dioxide fracturing fluid sand-carrying enhancer according to claim 1, It is characterized in that In step S22, the binary copolymer and CO in the mixed molecular model 2 The molecular number ratio is 1-10:500-1000; the shear motion model consists of upper and lower walls and an intermediate fluid layer. The intermediate fluid layer is a mixed molecular model, and the upper and lower walls are 316L stainless steel. The length, width, and height dimensions are respectively 5. The design and synthesis method of the supercritical carbon dioxide fracturing fluid sand-carrying enhancer as claimed in claim 4, It is characterized in that In step S22, the solubility of the polymer is determined by the simulation results of the radial distribution function, interaction energy and cohesive energy density parameters in the mixed molecular model; the viscoelasticity of the system is characterized by the viscosity increase multiple, elastic modulus and yield stress parameters to determine the sand carrying capacity of the polymer; the ability of the copolymer to reduce friction is determined by the friction shear stress; the safety and environmental protection of the copolymer is determined according to the safety and environmental protection rating parameters and the monomer price; and the best binary copolymer is selected by comprehensive weighting.
6. The design and synthesis method of the supercritical carbon dioxide fracturing fluid sand-carrying enhancer according to any one of claims 1 to 5, It is characterized in that Steps S1 and S2 are both completed using Materials Studio software.
7. A supercritical carbon dioxide fracturing fluid sand-carrying enhancer, It is characterized in that The method is prepared by the design and synthesis method as described in any one of claims 1 to 6.
